Da’wah Activities through Mountaineering: Multidisciplinary Overview of Pendaki Hijabers Community in Indonesia - Muhamad Agus Mushodiq; Suhono Suhono; Aprezo Pardodi Maba; Haikal Haikal; Ahmad Madkur (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
In Indonesia, da’wah activities have been implemented in various ways, including mountaineering. However, data showed that many mountain hikers in Indonesia had been seriously injured (even died) due to a lack of knowledge and preparation for hiking. This article aimed to analyze the goals of mountain hiking and fulfilling the reproductive health conducted by Pendaki Hijabers community members. The authors used a phenomenological approach with a descriptive-analytical type of qualitative research. The research was conducted at Mount Merapi and Prau Dieng, Indonesia, from 2019 until 2020 with 25 informants. The data were analyzed using Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) and Maqāşid al-Syarī'ah theory. The results showed that the goals of Pendaki Hijabers community activities varied, such as meditation on nature, exploration of nature verses ‘āyāt kauniyah’, da’wah through mountaineering, deepening mountaineering skills, eliminating negative stereotypes of hijab, ideological deconstruction of society through the hijab, and fighting developmentalism through social service, sport, education, and religious activities. Based on the CEDAW review, mountaineering for women, on the one hand, had a positive impact on psychology because it can eliminate double burden concepts and negative stereotypes for women. On the other hand, mountain hiking has a potential negative impact on women's reproductive health because luggage is too heavy, hiking during menstruation, and consumption of food and drinks that are not ideal. Based on the Maqāşid al-Syarī'ah review, mountaineering activities supported ḥifẓ dīn ‘safeguarding the religion’ because they are oriented towards the da’wah of Islam. But, mountaineering that does not pay attention to aspects of reproductive health potentially harms the goals of sharia in the form of ḥifẓ nafs ‘safeguarding the soul’ and ḥifẓ nasal ‘safeguarding offspring’.